A colecção egípcia do Museu de História Natural da Universidade do Porto : a estatueta de PTAH_SOKAR-OSIRIS - Sousa, Rogério Ferreira de (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The statuette of Ptah-Sokar-Osiris is one of the most interesting objects of the Egyptian collection of the Porto University Museum of Natural History. Besides offering a morphological and iconographical description of the small monument, this article also seeks to provide clues to understanding its religious meaning, as well as its ritual use.